Comparative Characteristics of Germination of Some Halophyte Plants in Saline Soils of Pavlodar Region - BEISENOVA, Raikhan; RAKHYMZHAN, Zhanar; TAZITDINOVA, Rumiya; AUYELBEKOVA, Almagul; KHUSSAINOV, Mansur (Journal of Environmental Management and Tourism, 2020)
The possibility of using halophytic plant species for remediation of saline soils in Kazakhstan is considered. In this regard, the purpose of our research is a comparative description of the germination of some halophytic plants of Pavlodar region in saline soils of European calf (salicornia europaea L.), Aksora (suaeda salsa Pall.), Tumpek sarzasan (halocnemum strobilaceum Pall.). The article aimed at selecting the most active seeds for the salt by germination indicator using some halophyte plants seeds. A comparative description of the germination of European calf (salicornia europaea L.), Aksora (suaeda salsa Pall.), Tumpek sarsazan (halocnemum strobilaceum Pall.) near Lake Maraldy of Pavlodar region was given. All of these plants have been shown to be true halophytes, and each of them can be used to reduce soil salinity. For this purpose, it can be recommended to the use European calf (salicornia europaea L.) of saline lands of not only in Pavlodar region, but in most saline areas of Kazakhstan.